Reflecting university image in the era of digitalization - Luque-Martínez, Teodoro; Faraoni, Nina; Doña-Toledo, Luis (Social Sciences & Humanities Open, 2026)
The digital transformation of Higher Education institutions affects their teaching, research, and administrative functions, ultimately shaping their public image. This study examines the factors that influence graduates' perceptions of university image, focusing on socio-demographic characteristics, university experience, employment-related outcomes, and digitalization dimensions such as information quality, online communication, learning quality, social media presence, and electronic Word of Mouth (e-WOM). A nationwide survey was conducted among 600 Spanish graduates using structured questionnaires with validated scales. Data were analyzed using binary logistic regression. The findings reveal that graduate identification with the institution, the quality of shared information and websites, and e-WOM is significantly associated with the perceived image. Additionally, job market insertion plays a crucial role. The findings suggest the relevance of strategically managing digital presence and communication, especially on social media. By integrating digitalization into image-building strategies, the study offers a novel framework for understanding how institutional image is constructed in the digital era.
Keywords: digitalization; university image; higher education; alumni; COVID; logistic regression